Respuesta :

Answer:

(1, -8)

Step-by-step explanation:

Solve by Substitution

9x − y = 17 and 5x + 4y = −27

Solve for y in the first equation.

y = −17 + 9x 5x + 4y = −27

Replace all occurrences of y with −17 + 9x in each equation.

Replace all occurrences of y in 5x + 4y = −27 with −17 + 9x. 5x + 4 (−17 + 9x) = −27

y = −17 + 9x

Simplify 5x + 4 (−17 + 9x).

41x − 68 = −27 y = −17 + 9x

Solve for x in the first equation.

Move all terms not containing x to the right side of the equation.

41x = 41

y = −17 + 9x

Divide each term by 41 and simplify.

x = 1

y = −17 + 9x

 

Replace all occurrences of x with 1 in each equation.

Replace all occurrences of x in y = −17 + 9x with 1. y = −17 + 9 (1)

x = 1

Simplify −17 + 9 (1).

y = −8

x = 1

The solution to the system is the complete set of ordered pairs that are valid solutions.

(1, −8)

The result can be shown in multiple forms.

Point Form:

(1, −8)

Equation Form:

x = 1, y = −8

Нугцлцьцьцьцзцзц цшцгаривбвбы
ACCESS MORE